Chapiniella variabilis (nematoda) parasitizing chelonoidis carbonarius and C. denticulatus (testudinidae) in the state of Piauí - Freire, Simone Mousinho; Leal, Anangela Ravena da Silva; Knoff, Marcelo; Gomes, Delir Corrêa; Dos Santos, Jeannie Nascimento; Giese, Elane Guerreiro; Da Silva, Reinaldo José [UNESP]; Mendonça, Ivete Lopes (FapUNIFESP (SciELO), 2017)
Chapiniella variabilis (Chapin, 1924), a strongylid nematode, was collected parasitizing the large intestine of the tortoises Chelonoidis carbonarius (Spix, 1824) (Cc) and C. denticulatus (Linnaeus, 1766) (Cd) in the Zoobotanical Park of the municipality of Teresina, state of Piauí, Brazil. The taxonomic identification was based on morphological and morphometric features, using bright-field and scanning electron microscopy. The present study adds new observations on the morphology, mainly relating to the mouth papillae, external and internal leaf-crown elements, excretory pore, deirids and male and female posterior end. The parasitic indices of prevalence (P), mean intensity (MI), mean abundance (MA) and range of infection (RI) of C. variabilis in these two tortoise species were: P = 100%, MI = 833.3, MA = 833.3, RI = 500-1,500 (Cc); P = 100%, MI = 472.2, MA = 472.2, RI = 333-500 (Cd). This record expands occurrences of C. variabilis to a new host, C. carbonarius, and to another state in Brazil, in the Neotropical region of South America. Adjustment to host management with the aim of improving hygiene and health conditions is suggested.
Chapiniella variabilis (nematoda) parasitando chelonoidis carbonarius e C. denticulatus (testudinidae) do estado do Piauí
Keywords: Brazil; Chapiniella variabilis; Nematode; Strongylid; Testudinid